Evaluation of the risks for animal health related to the presence of hydroxymethylfurfural (HMF) in feed for honey bees. (20th April 2022) - ; Bodin, Laurent; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Leblanc, Jean‐Charles; Bignami, Margherita; Hoogenboom, Laurentius (Ron); Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; Petersen, Annette; et al.
Abstract: The European Commission has asked the EFSA to evaluate the risk for animal health related to the presence of hydroxymethylfurfural (HMF) in honey bee feed. HMF is a degradation product of particular sugars and can be present in bee feed. HMF is of low acute toxicity in bees but causes increased mortality upon chronic exposure. A benchmark dose lower limit 10% (BMDL10 ) of 1.16 μg HMF per bee per day has been calculated from mortalities observed in a 20‐day study and established as a Reference Point covering also mortality in larvae, drones and queens for which no or insufficient toxicity data were available. Winter bees have a much longer lifespan than summer bees and HMF shows clear time reinforced toxicity (TRT) characteristics. Therefore, additional Reference Point intervals of 0.21–3.1, 0.091–1.1 and 0.019–0.35 µg HMF/bee per day were calculated based on extrapolation to exposure durations of 50, 90 and 180 days, respectively. A total of 219 analytical data of HMF concentrations in bee feed from EU Member States and 88 from Industry were available. Exposure estimates of worker bees and larvae ranged between 0.1 and 0.48, and between 0.1 and 0.51 μg HMF/per day, respectively. They were well below the BMDL10 of 1.16 μg HMF/bee per day, and thus, no concern was identified. However, when accounting for TRT, the probability that exposures were below established reference point intervals was assessed to be extremely unlikely to almost certain depending on exposure duration. A concern for bee health was identified when bees are exposed to HMF contaminated bee feed for several months.